2011
DOI: 10.3390/medicina47100082
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Body Composition of 9- and 10-Year-Old Children in Latvia

Abstract: Background and Objective. According to the data of epidemiologic research, the prevalence of both excessive and insufficient body weight is increasing in a pediatric population leading to the growing burden of health problems due to these changes. The aim of the study was to understand the current situation of physical development of 9- and 10-year-old boys and girls in Latvia and to estimate the prevalence of underweight, normal weight, overweight, and obesity among young adolescents. Material and Methods. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…The results of this study show that 30% of the children studied were characterized by abnormal body weight. The authors point out that it was not only overweight and obesity that was a problem, but underweight, which was equally common ( 27 ). The study by Kobylinska et al found similar results in terms of BMI in traditional elementary school students, with 57.5% of the subjects having normal body weight, 21.5% overweight, and 21% underweight.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study show that 30% of the children studied were characterized by abnormal body weight. The authors point out that it was not only overweight and obesity that was a problem, but underweight, which was equally common ( 27 ). The study by Kobylinska et al found similar results in terms of BMI in traditional elementary school students, with 57.5% of the subjects having normal body weight, 21.5% overweight, and 21% underweight.…”
Section: Discussionmentioning
confidence: 99%
“…Latvijā ir veikti vairāki pētījumi, kur ir noskaidrots bērnu ĶMI. Karklina et al, (2011) bērniem vecumā no 9 līdz 10 gadiem no dažādiem Latvijas reģioniem noteica, ka vairāk kā pusei zēnu un meiteņu ir normāls svars, bet apmēram vienai piektdaļai zēnu un meiteņu 10 gadu vecumā ir samazināts svars. Savukārt 28,3 % meiteņu 9 gadu vecuma ir palielināts svars.…”
Section: ķErmeņa Masas Indeksa Noteikšana Bērniemunclassified
“…The fat free mass index (FFMI) and fat mass index (FMI) are considered to be better markers of excess weight than BMI (Karklina et al, 2011). Because of the study design, we had no access to FFMI or FMI.…”
Section: Limitationsmentioning
confidence: 99%